Mercato e facoltà della prassi. Per un′antropologia dolciaria - Mazzeo, Marco (Dialogoi. Rivista di studi comparatistici, 2020)
The importance that today the culinary activities have assumed in the production scene could be misleading and suggest a redemption of the so-called “minor senses” (taste, smell) within the Western vision of the body. On the contrary, the article will try to show that the centrality of cooking in the contemporary world does not focus on sensorial perception but on the exaltation of the practical faculties involved in culinary activities and on its possible use in the neoliberal world. This thesis will be argued through the analysis of a traditional recipe and the way in which it has been used in a well-known television format.